Dilatation Treatment for Esophageal Strictures - Zakiah Zakiah; Ana Mira Lubis; Marcellus Simadibrata; Nurmiati Amir (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
A patient with adjustment disorder and depression had experienced a suicide temptation by ingesting corrosive substance since 6 months before her hospital admission. On the first day care, she only can swallow “soft-fluid diet” which is given very slowly. Subsequently, the patient had a series of dilatation treatment guided by fluoroscopy and demonstrated a very impressive result. On the first dilatation, a 7 mm dilator was used, and then respectively 9, 10, 5, 12, 8 and 14 mm dilator was applied. We needed to perform three sessions of dilatation until the 9 mm dilator can be inserted. After the second dilatation, the patient had started to be able to eat refine porridge and subsequently rice porridge with soft vegetables and side dishes. At the end of treatment, she had already been able to eat normally. The general management of esophageal stricture by using dilator will be discussed in this article.   Keywords: stricture, corrosive substance, dilatation treatment, dysphagia